Antiobesity efficacy of asiatic acid: down-regulation of adipogenic and inflammatory processes in high fat diet induced obese rats. (19th October 2020) - Uddandrao, V. V. Sathibabu; Rameshreddy, P.; Brahmanaidu, P.; Ponnusamy, Ponmurugan; Balakrishnan, Santhanaraj; Ramavat, Ravindar Naik; Swapna, K.; Pothani, Suresh; Nemani, Harishankar; Meriga, Balaji; Vadivukkarasi, S.; P. R., Nivedha; et al.
Abstract: In the current study, we evaluated the effects of Asiatic acid (AA) on lipid metabolic markers in HFD-induced obese Sprague-Dawley rat model. AA (20 mg/kg BW) was administered orally to HFD-fed rats for 42 days. Changes in body composition, glucose, insulin resistance (IR) and lipid profiles of tissues, plasma and the pattern of gene expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) and its target genes fatty-acid synthase (FAS), adipocyte protein-2 (aP2) and uncoupling protein-2 (UCP-2) and pro-inflammatory factor tumor necrosis factor (TNF)-α were observed in experimental rats. Oral administration of AA exerts therapeutic effects similar to orlistat in attenuating body weight gain, glucose, IR, plasma and tissue lipids and mRNA levels of PPAR-γ, FAS, aP2 and inflammatory factor TNF-α and increasing UCP-2 expression in HFD-fed rats. Hence, these findings concluded that AA attenuate HFD-induced obesity by modulating PPAR-γ and its target genes and regulate lipid metabolism, suggesting their possible antiobesity effects.